A Novel Solution to Sieving Model for a Drilling Fluid Shale Shaker - WeiBing Zhu; WaNi Wu; Xu Hao; HeShun Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
According to the principle of hydromechanics, the flow characteristic of drilling fluid on the screen is studied. In consideration of affecting factors, sieving model equations including kinematic equations and continuity equation for drilling fluid shale shaker are established. This paper shows a novel solution to the sieving model equations by using average energy principle and finite differential method. The computer simulation program of flow capacity of the shaker is developed. The model will be of great significance in evaluating screening performance and screen selection. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1399